Fruit waste adsorbent for ammonia nitrogen removal from synthetic solution: isotherms and kinetics - Abu Zahrim Yasser; Y. Lija; L. N. S. Ricky; Azreen Ibrahim (2016)
In this study, four types of watermelon rind (WR) adsorbents; fresh WR, modified WR with sodium hydroxide (NaOH), potassium hydroxide (KOH) and sulphuric acid (H2SO4) were used as a potential low-cost adsorbent to remove NH3-N from solution. The adsorption data were fitted with the adsorption isotherm and kinetic models to predict the mechanisms and kinetic characteristics of the adsorption process. The equilibrium data agreed well with Langmuir isotherm model with highest correlation (R2=1.00). As for kinetic modelling, the adsorption process follows pseudo-second order for all four types of adsorbents which has R2 value of 1.0 and calculated adsorption capacity, Qe of 1.2148mg/g. The calculated Qe for pseudo-second order has the smallest difference with the experimental Qe and thus suggest that this adsorption process is mainly governed by chemical process involving cations sharing or exchange between WR adsorbent and NH3-N in the solution.